The Influence of Entrepreneurship Education, Self-Efficacy, and Risk-Taking Behavior on Entrepreneurial Intentions Among Generation Z Students, with Entrepreneurial Character as a Mediating Variable - Supatminingsih, Tuti; Sukmawati; Ahmad, M. Ihsan Said; Thamrin, Muh. Ilyas (Indonesian Journal of Economic & Management Sciences, 2024)
This study, using entrepreneurial character as a mediating variable, seeks to learn more about how entrepreneurial education, self-efficacy, and risk-taking behavior influence entrepreneurial intention in Generation Z college students. The study sample consisted of 100 students from the Faculty of Economics and Business, UNM. The data were examined using partial least squares structural equation modeling (PLS-SEM). The study found that entrepreneurial education, self-efficacy, and risk-taking behavior all had a significant impact on entrepreneurial intention, which was moderated by entrepreneurial character.